2019
DOI: 10.1017/jfm.2019.317
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and evolution of turbulent Taylor rolls

Abstract: In many shear-and pressure-driven wall-bounded turbulent flows secondary motions spontaneously develop and their interaction with the main flow alters the overall largescale features and transfer properties. Taylor-Couette flow, the fluid motion developing in the gap between two concentric cylinders rotating at different angular velocity, is not an exception, and toroidal Taylor rolls have been observed from the early development of the flow up to the fully turbulent regime. In this manuscript we show that und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 33 publications
9
45
0
Order By: Relevance
“…Here, we can see that the flow self-organizes in Taylor rolls as the Coriolis force starts to become dominant, i.e. when (Sacco et al 2019). As increases, we first observe that the rolls become sharper and more prominent, as evidenced by an increment in , which is also observed in the experiments (see figure 5).…”
Section: Boundary Layer Transitions and State Switchingmentioning
confidence: 86%
See 1 more Smart Citation
“…Here, we can see that the flow self-organizes in Taylor rolls as the Coriolis force starts to become dominant, i.e. when (Sacco et al 2019). As increases, we first observe that the rolls become sharper and more prominent, as evidenced by an increment in , which is also observed in the experiments (see figure 5).…”
Section: Boundary Layer Transitions and State Switchingmentioning
confidence: 86%
“…In this study we set out to globally and locally probe the angular momentum transport in a wide range of driving strength for the case of low curvature , focusing in particular in the range , where the transition to the ultimate regime happens, and where Brauckmann & Eckhardt (2017) observed the appearance of two peaks for angular momentum transport using numerical simulations. The main motivation of this study is to elucidate the link between the change in behaviour of the dependence (Martinez-Arias et al 2014), the vanishing of the broad peak and the changing role of vortical motions (Sacco, Verzicco & Ostilla-Mónico 2019) which all happen around this transition. We will use an experimental set-up with very large aspect ratios , which allows for the flow to switch between states, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult not to be reminded by the discussion above of other examples of spontaneous stream formation in more complicated flows. The best known are probably the streaks in wall-bounded turbulence and other shear flows (Tsukahara, Kawamura & Shingai 2006;Dong et al 2017;Jiménez 2018a), and the azimuthal jets of planetary atmospheres and rotating flows (Maltrud & Vallis 1991;Dritschel & McIntyre 2008;Grossmann, Lohse & Sun 2016;Sacco, Verzicco & Ostilla-Mónico 2019). In many of these cases, the streams are a streamwise concatenation of smaller units (Lozano-Durán, Flores & Jiménez 2012), and the question arises of how these units organise longitudinally.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze these structures more quantitatively, we proceed in an analogous manner to Sacco et al (2019). Secondary flows are captured through the streamwise vorticity, as they are perpendicular to the main flow direction.…”
Section: The Effect Of Rotation On Large-scale Structuresmentioning
confidence: 99%
“…This means that something else aside from centrifugal effects must play a role. Numerical studies of Taylor-Couette flow conducted by Sacco, Verzicco & Ostilla-Mónico (2019) found that turbulent Taylor rolls appeared with a combination of shear and mild anticyclonic rotation. Their onset was not controlled by the curvature of the system.…”
Section: Introductionmentioning
confidence: 99%